Hypoxic hepatitis in an extensive aortic disecction: case report - Bellido-Caparó, Alvaro (2019)
Hypoxic hepatitis is an uncommon cause of hepatic damage characterized by a centrolobular necrosis. Its pathophysiology remains unclear. Aortic dissection is a rare but frequently catastrophic event. It is caused by an aortic intimal tear with propagation of a false channel in the media. Depending on the site and extension, it can cause hypoperfusion of any organ leading to cellular ischemia and necrosis. We are presenting a case of hypoxic hepatitis in a patient with an extensive aortic dissection who present to the emergency department.